Membangun Karakter Enterpreneurship Santri Melalui Pengembangan Potensi Pondok Pesantren Assholah Kajeron - Lailatus Sa'ida; Nikmatul Izzah; M. Asif nur Fauzi; Nuruddin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
The purpose of the research, Building Student Entrepreneurial Character Through Capacity Building of Assholach Kajeron Islamic Boarding School, is to describe the development of student entrepreneurial character through Capacity Building of Assholach Kajeron Islamic Boarding School. With the hope of self-development of students in Pasuruano not only with cognitive competence but also with entrepreneurial skills. Santripreneur is a development the empowerment model of enterpreneurial students that combines four main elements,: kyai ( teacher) ,students, curriculum,infrastructure, the fourth element in assholach boarding school gas cinsiderable potential .this potential can be optimized when the four elements of mutual are being synergy .full support of kyai ( teacher) for the student to take advantage of infrastructure ( economic potential) with a network of partner Schools can be packaged through pesantren curriculum in madrasah Diniyyah. Which allows student to become entrepreneur to create economically independent students. In collaboration with practitioner in the creative industry field,aims to be create santripreneur in creative industries, who can better manage their bussines. This activity is divided into three activities namely socialization ,traning,and mentoring . Keyword: Entrepreneurial Character, Santri, Islamic Boarding School Potential